Understanding the familial strategies of emancipation of former slaves in Bura, Kenya, early 20th century - (:unkn) unknown (My University, 2023)
In 1892, the Catholic priests of the Congregation of the Holy Spirit decided to set up a mission in Bura, on the Dabida hill, few years before the creation of the East Africa Protectorate. They took with them a dozen young couples of former slaves who had been ransomed by the priests in Bagamoyo Catholic station (German East Africa). During the first years, the missionaries' policy, supported by the help of former slaves, perpetuated numerous acts of violence against the inhabitants of the region (spoliation of land, etc.). The latter, in return, did not hide their hostility towards the mission in a context of emphasising community ties and redefining identities after the settling of Europeans, episodes of great famine and new types of migratory movements. These events influenced the choices of the former slaves and their descendants, in their emancipation and in the creation of a common identity. They tried to find a better future in a place where the support to Christians was not well seen, relying on the advantages given by the mission or seeking their fortune elsewhere, migrating to Nairobi or to Tanganyika.Up to today, the historiography of the Taita hills never took into consideration the impact of slavery on the personal lives of some inhabitants of the region. This contribution to the history of the Christian villages of former slaves in East Africa, tries to understand the logics of emancipation of these former slaves and their descendants in the first decades of the 20th century.
Keywords: African Research